Can ASEAN retain centrality in Indo-Pacific region? - From a GVC point of view - Masataka Fujita (Journal of Contemporary East Asia Studies, 2021)
The crucial determinant factor for ASEAN to support the Indo-Pacific strategy is whether ASEAN can retain and exercise the centrality. This paper addresses the issue on the centrality as to whether ASEAN can retain its centrality in the Indo-Pacific region. The issue is whether ASEAN can continue to assume an important position in Indo-Pacific economic transactions, more specifically in global value chains (GVCs) in the Indo-Pacific region. As GVC is expected to reflect the economic integration and interconnectivity of the region, higher participation of ASEAN in the Indo-Pacific GVC as compared with its own GVC, or at least a similar level of participation, is considered as retention of centrality. However, the reality is not such the case, and ASEAN is losing its centrality in the Indo-Pacific region in terms of GVC participation. This is partly due to the fact that Indo-Pacific is less integrated than ASEAN. Under this situation, the paper provides some policy implications for ASEAN to retain the centrality in Indo-Pacific. One of such policies is to increase and promote foreign direct investment (FDI) as it is the key to create GVCs. FDI flows as percentage of GDP in Indo-Pacific is much smaller in Indo-Pacific than in ASEAN.